Fostering Language Learning in the University EFL Classroom through Literature: A Task-Based Approach (GIST – Education and Learning Research Journal, 2019)
The role of literature as a teaching and learning tool in English as a Foreign Language has long been acknowledged. Literary texts offer teachers opportunities to provide students with authentic materials to heighten their motivation by involving them in challenging Task-Based activities in which they interact with authors and learn about features of these authors’ society. The purpose of this research study was to   investigate the role of literature as a pedagogical tool in the EFL class and see how this can be advantageous in fostering learners’ language skills and intercultural awareness.  The sample population encompassed 26 sixth-semester students enrolled in a Reading course who are completing their BA in Foreign Languages at a public University in Colombia. A semi-structured questionnaire and a Reading Guide were designed to elicit information from students who were asked to read an unabridged English language fiction novel. The findings show that the participants’ motivation to complete the Task-Based Reading and Writing Project was high as well as their language skills.Keywords. EFL, ESL, Task-Based Approach, Literature, intercultural Communicative Competence
Keywords: EFL; ESL; Task-Based Approach; Literature; intercultural Communicative Competence